Wyrażenia algebraiczne
27. 7/12(1/7a+4/12b)+9/10(⅓a-5/6b) =
28. 1/18(⅔a-9/4b)-1/23(43a-8b0 =
29.1,1(1,1a-1,2b)+1,2(1,2a+1,1b) =
30. 2,5x²-[0,6x²+(3,5x+x²)+(x²+3x)]+[0,1x²-(x²-3,5x)+x²] =
31. x-1,4xy+1,2y-{1,6xy-[0,6y-(1,4x-2,4xy)]-(1,4xy-16y)} =
32. 2,6x-{1,8y-[2,2x-(j-0,6x)+1,4y]-[1,6x-0,2x]} =
33.3x×[5y-(7x-4y)]-8y+[3x-7y-5x)+(6x-11y)] =
34. x²[4,8x²-0,6y(1,6x-1,4y)]-1,2y²×[3,6x²-1,6x(0,8x-1,4y)+2,4y²] =
35. 1⅓x×[4½x-(3¾y-31½)]-[13⅓x-(113/7-8⅓y)]×4⅕y =

1

Odpowiedzi

2010-02-27T23:13:39+01:00
27.
7/12(1/7a+4/12b)+9/10(⅓a-5/6b) =
1/12a+7/36b+3/10a-3/4b=
5/60a+7/36b+18/60a-9/36a=
-2/36b+23/36a=
-1/18b+23/36a

28.
1/18(⅔a-9/4b)-1/23(43a-8b) =
1/27a-1/8b+43/23a+8/23b=
23/621a-23/184b-1161/621a+64/184b=
-1138/621a+47/184b

29.
1,1(1,1a-1,2b)+1,2(1,2a+1,1b) =
1,21a-1,32b+1,44a+1,32b=
2,65a

30.
2,5x²-[0,6x²+(3,5x+x²)+(x²+3x)]+[0,1x²-(x²-3,5x)+x²] =
2,5x²-(0,6x²+3,5x+x²+x²+3x²)+(0,1x²-x²+3,5x+x²)=
2,5x²+4,4x²-3,5x+1,9x²+2,5x=
8,8x²-x

31.
x-1,4xy+1,2y-{1,6xy-[0,6y-(1,4x-2,4xy)]-(1,4xy-16y)} =
x-1,4xy+1,2y-[1,6xy-(0,6y-1,4x+2,4xy)-1,4xy+16y)=
x-1,4xy+1,2y-(1,6xy-0,6y+1,4x-2,4xy-1,4xy+16y)=
x-1,4xy+1,2y-1,6xy+0,6y-1,4x+2,4xy+1,4xy-16y=
-0,4x-4xy+17,8y

32.
2,6x-{1,8y-[2,2x-(j-0,6x)+1,4y]-[1,6x-0,2x]} =
2,6x-[1,8y-(2,2x-y+0,6x+1,4y)-1,6x+0,2x]=
2,6x-(1,8y-2,2x+y-0,6x-1,4y-1,6x+0,2x)=
1,6x-1,8y+2,2x-y+0,6x+1,4y+1,6x-0,2x=
5,8x+2,2y

33.
3x×[5y-(7x-4y)]-8y+[3x-7y-5x)+(6x-11y)] =
3x*(9y-7x)-8y+3x-7y-5x+6x-11y=
27y-21x-8y+3x-7y-5x+6x-11y=
y-17x

1 5 1